The correlation between television news credibility and the level of fear of crime - Badr ElDin, Nahla (AUC Knowledge Fountain, 2013)
After the police withdrawal in January 2011 from Egypt’ streets, Egyptians tasted another level of fear of crime. Media coverage played a visible role in heightening people’s fear of crime with its intensive and completely uncensored coverage of crime scenes. Nowadays, it has become a common TV News practice to show footage of dead bodies and graphic scenes of violent acts during riots. This study attempted to explore the extent to which scenes of people getting assaulted, kidnapped, tortured, and killed on air cultivates fears inside viewers, specifically youth. The concept resonance occurs when the impact of television amplifies with the real life facts of a specific social group, an example of which is local news broadcasting numerous violent messages related to viewers’ communities which are dissimilar to real crime rates (Morgan & Shanahan, 2010). The results of a sample of 154 undergraduate Egyptian students enrolled at the American University in Cairo showed that the Resonance Hypothesis was observed solely in female students who experienced crime in real life in response to TV newscasts only rather than Talk Shows. These females showed a moderate correlation between TV newscast credibility and the level of fear of crime. The rest of the sample did not show any correlation between TV news credibility and the level of fear of crime.